From the Anthropological Machine to the Animal Crisis - Vadilonga Gattermayer, Michele (Filosofia Morale/Moral Philosophy, 2024)
In this essay, I will reconstruct the biopolitical framework regarding human-animal relations, through the device of boundary production Agamben called the “anthropological machine”. I will argue that the effects of the machine can be more extensively grasped on the constitutive outside of the human, namely animals and that the current status of institutionalised relationships with animals, gathered under the name of “animal crisis”, can be framed as a direct effect of the separation.